2004
DOI: 10.4049/jimmunol.172.5.3280
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Infusion Promotes Rapid Complement Depletion and Acute CD20 Loss in Chronic Lymphocytic Leukemia

Abstract: Complement plays an important role in the immunotherapeutic action of the anti-CD20 mAb rituximab, and therefore we investigated whether complement might be the limiting factor in rituximab therapy. Our in vitro studies indicate that at high cell densities, binding of rituximab to human CD20+ cells leads to loss of complement activity and consumption of component C2. Infusion of rituximab in chronic lymphocytic leukemia patients also depletes complement; sera of treated patients have reduced capacity to C3b op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
342
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 321 publications
(361 citation statements)
references
References 48 publications
17
342
1
1
Order By: Relevance
“…The role of complement-dependent cytotoxicity (CDC) is suggested by the consumption of complement observed after rituximab administration but in vitro CDC does not correlate with clinical response in lymphomas (Winkler et al, 1999;Weng and Levy, 2001). However, CDC seems to be the most important mechanism of cell lysis in chronic lymphocytic leukemia (CLL) patients (Kennedy et al, 2004). CDC is probably involved in the cytokine-release syndrome and its toxicity (Bienvenu et al, 2001).…”
Section: Mechanisms Of Action Of Rituximabmentioning
confidence: 99%
“…The role of complement-dependent cytotoxicity (CDC) is suggested by the consumption of complement observed after rituximab administration but in vitro CDC does not correlate with clinical response in lymphomas (Winkler et al, 1999;Weng and Levy, 2001). However, CDC seems to be the most important mechanism of cell lysis in chronic lymphocytic leukemia (CLL) patients (Kennedy et al, 2004). CDC is probably involved in the cytokine-release syndrome and its toxicity (Bienvenu et al, 2001).…”
Section: Mechanisms Of Action Of Rituximabmentioning
confidence: 99%
“…This poor efficacy has been explained by low CD20 expression levels of CLL cells, 9,10 the presence of complement inactivating molecules (CD55, CD59) on CLL cells, 11 the presence of soluble CD20 (ref. 12), shaving and downmodulation of CD20 after rituximab treatment, 13,14 resistance to antibody dependent cellular cytotoxicity by natural killer cells in vitro 15 andFlast but not leastF the intrinsic anti-apoptotic profile of CLL cells. 16 In this study, we show that, in sharp contrast to the induction of resistance to cytotoxic drugs, CD40 stimulation of CLL cells considerably increases sensitivity to anti-CD20-mediated cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive preclinical evidence showed that it is neither internalized nor shed when bound to B cells (9,27,33). We recently reported that during the standard infusion of RTX in patients with chronic lymphocytic leukemia (CLL), a large fraction of B cells was rapidly cleared from the circulation after only 30 mg of RTX was infused (34). However, immediately after the total dose of ϳ700 mg of RTX had been infused, when the concentration of RTX in the bloodstream was quite high (Ͼ100 g/ml), substantial B cell recrudescence was evident.…”
Section: T Argeting Of Ags On Cancer Cells By Mabs Has Been a Key Strmentioning
confidence: 99%